WEST EUROPEAN ORIGINS OF A. D. GRADOVSKIY’S LEGAL THEORY - Gulyak, Ivan; Zolotarev, Sergey; Gusynin, Nikolay; Zolotareva, Tatyana (Revista Inclusiones, 2020)
The topicality of the issue is due to the acute necessity to elaborate the thoroughly substantiated conception of the further reforming in today’s Russia. The reforms can only be implemented successfully under the condition of developing an adequate legal system. At the same time, modernization of political institutions would be impossible without further systematization of the Russian law. The optimal basis for such modernization is the creative theoretical synthesis of the Russian law with West European legal ideas and concepts. Certainly, we do not speak of the fundamental change of the basic laws of the Russian Federation, but about such theoretical synthesis which would open an immediate opportunity for the evolution of political institutions towards forming a constitutional system embodying the best conceptual developments of the past and present.